The Reciprocal Paradigm of TafsÄ«r al-Miá¹£bah and TafsÄ«r al-Taá¸¥rÄ«r wa al-TanwÄ«r on Surah al-Baqarah verse 222 about Menstruation Blood - Millati, Halya (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2021)
Misogynistic interpretation of women on their menstruation period as